Farmer’s judicial recovery in Brazil – A dialogue between law, economics and business - Alves, André Luiz Aidar; Teixeira, Sônia Milagres; Cruz, José Elenilson (Seven Editora, 2023)
The work promotes a historical-normative-conceptual analysis of the judicial reorganization of rural producers in Brazil, involving Law, Economics and Administration. Although it occurs through a judicial process, this is a complex way of solving the economic crisis of the rural debtor that requires the participation of various professionals, such as economists, administrators, accountants, and others. With judicial reorganization, an organizational structure is created, autonomous in relation to the figure of the debtor, which acts not only in the process, but also in the market, by specific rules and which requires management with maximum efficiency in the pursuit of its objectives. DOI:https://doi.org/10.56238/sevened2023.006-021